Q. 15.0( 5 Votes )

If f : R <span la

Answer :

we have f(x) = (3 - x3)1/3

f(x) = (3 - x3)1/3


f(f(x)) = [3 - {(3 - x3)1/3}3]1/3


fof(x) = [3 - (3 - x3)]1/3


= [3 - 3 + x3)1/3


= (x3)1/3


Hence, fof(x) = x


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar